Simbol: Arti, Fungsi, dan Implikasi Metodologisnya - Eko Punto Hendro (Endogami: Jurnal Ilmiah Kajian Antropologi, 2020)
Sign consists signifier and signified, but other expert tell that relationship between signs and their object are iconic, indexial and symbolic. The relationship signifier and signified is convention and arbitrary, but it can also be denotative, connotative and myth. Culture can means a set symbol system, which is used by mansion or people for ruler their behavior, included adaptation and interaction with their physical and symbolic environment. Interpretation to know the symbolic meaning, it is focus of symbolic interpretivism paradigm and also hermeumeutic paradigm, wich both also focus to interpretation of human creation